Attachment style and leader-member exchange: The role of effort to build high quality relationships. Issue 3 (2nd May 2017) - Maslyn, John M.; Schyns, Birgit; Farmer, Steven M.
Abstract : Purpose: The purpose of this paper is to examine psychological attachment styles (secure, anxious, and avoidant) as antecedents to leader-member exchange (LMX) quality both directly and through their impact on employees' efforts to build high quality LMX relationships. Employees with secure attachment styles are proposed to be successful at building high quality LMX relationships while employees with anxious and avoidant styles are proposed to display the opposite effect. Design/methodology/approach: Data were collected through a survey of 213 employees nested in 37 work groups. Hypotheses were tested using multilevel modeling within MPlus. Findings: Results indicated that secure and anxious attachment styles were associated with LMX only by impacting the exertion of effort specifically aimed at relationship development with the manager. Alternatively, the avoidant style was directly and negatively linked to LMX but not associated with effort undertaken to build a high quality relationship. Practical implications: The effects of attachment style on effort to develop high quality LMX relationships reveal that subordinate attachment style may impact those subordinates' ability and interest in developing positive LMX relationships. Therefore, managers may need to purposively deviate from typical LMX development processes in order to create a more conducive environment for developing high quality relationships with subordinates of differing attachment styles. Originality/value: This study is one of the first to examine the mediating impact of effort to build high quality LMX relationships given personal propensities (attachment style) to form relationships in the workplace.